2017
DOI: 10.1038/s41598-017-15532-0
|View full text |Cite
|
Sign up to set email alerts
|

Systems analysis of latent HIV reversal reveals altered stress kinase signaling and increased cell death in infected T cells

Abstract: Viral latency remains the most significant obstacle to HIV eradication. Clinical strategies aim to purge the latent CD4+ T cell reservoir by activating viral expression to induce death, but are undercut by the inability to target latently infected cells. Here we explored the acute signaling response of latent HIV-infected CD4+ T cells to identify dynamic phosphorylation signatures that could be targeted for therapy. Stimulation with CD3/CD28, PMA/ionomycin, or latency reversing agents prostratin and SAHA, yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 48 publications
6
26
0
Order By: Relevance
“…We also observed an upward trend in the mRNA expression of the innate antiviral signalling pathway components RIG-I and MAVS in the vRNA high fraction, consistent with previous work demonstrating HIV-1 vRNA's ability to activate these pathways ( Supplementary Fig. 1e and f) 17,18 . Our data therefore indicates that in a preliminary screening model of HIV-1 latency, DDX3 inhibition with RK-33 results in latency reversal and that the RK-33-treated HIV-1 expressing cells harbour markers for apoptosis and are more susceptible to cell death by RK-33 than the vRNA-/GFP-J-Lat 11.1 cells or uninfected parental Jurkat cells.…”
Section: Ddx3 Inhibition Induces Reactivation and Cell Death In J-latsupporting
confidence: 91%
“…We also observed an upward trend in the mRNA expression of the innate antiviral signalling pathway components RIG-I and MAVS in the vRNA high fraction, consistent with previous work demonstrating HIV-1 vRNA's ability to activate these pathways ( Supplementary Fig. 1e and f) 17,18 . Our data therefore indicates that in a preliminary screening model of HIV-1 latency, DDX3 inhibition with RK-33 results in latency reversal and that the RK-33-treated HIV-1 expressing cells harbour markers for apoptosis and are more susceptible to cell death by RK-33 than the vRNA-/GFP-J-Lat 11.1 cells or uninfected parental Jurkat cells.…”
Section: Ddx3 Inhibition Induces Reactivation and Cell Death In J-latsupporting
confidence: 91%
“…We recently reported that the antibiotic anisomycin, a potent activator of the p38 and JNK MAPK pathways, increased both p-p38 and p-JNK activation within 30 minutes and cell death at 24 hours in virus-exposed TCM cells relative to uninfected cells (29). We found that anisomycin treatment increased levels of p-p53 and CC3 to a greater extent in virus-exposed cells relative to uninfected cells, and that this could be reversed with p38 inhibition ( Fig.…”
Section: Pro-apoptotic Activity Of P-p38 and P53 Is Enhanced In Virussupporting
confidence: 50%
“…We previously showed that TCR stimulation via CD3/CD28 leads to more cell death in latent HIV-infected CD4+ central memory-like T cells infected in vitro relative to uninfected cells (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To classify HIV+, T-cell depleted, and healthy PBMC samples, partial least squares discriminant analysis (PLS-DA)– which identifies linear combinations of variables to maximally separate known biological states –identified classification signatures based on measurements of 16 cytokines and chemokines, and then the underlying molecular changes could be associated with each group [39]. In a study from our lab, we measured phospho-signaling differences in uninfected and latent HIV-infected T cells and used PLS-DA to define signatures that predicted infection status and then identified changes in stress kinase signaling as a novel target for preferential infected-cell killing [40]. Comparing total immune cell composition in healthy and infected donors, SPADE and t-SNE analyses performed on 26-parameter mass cytometry data demonstrated that infected patients had a higher fraction of highly differentiated effector memory cells following HIV infection and ART treatment in comparison to healthy donors [41].…”
Section: Connecting Immune Cell States and Composition With Outcomesmentioning
confidence: 99%